Fourth ERCIM workshop on e-mobility - Brogle, Marc; Osipov, Evgeny; Braun, Torsten; Heijenk, Geert (Luleå tekniska universitet, Datavetenskap, 2010)
ERCIM, the European Research Consortium for Informatics and Mathematics, aims to foster collaborative work within the European research community and to increase co-operation with European industry. In the ERCIM eMobility workshop, current progress and future developments in the area of eMobility should be discussed and the existing gap between theory and application closed. This volume contains all accepted papers of the fourth eMobility workshop, which has been held in Luleå, Sweden, on May 31, 2009. Papers from different areas have been selected for this workshop. The contributions discuss several topics of the ERCIM eMobility working group including, testbeds for mobile networks, performance optimization for cellular networks, QoS in V2B communication, reliability in ad-hoc networks, distributed resource discovery and use, traffic generation models for wireless networks, IMS clients, ICT support for mobility, VANETs, and mobile video conferencing.At this point, we want to thank all authors of the submitted papers and the members of the international program committee for their contribution to the success of the event and the high quality program. The proceedings are divided into two sections, full papers and short papers. While the latter present work in progress and ongoing research, the full papers have been carefully selected in a peer review process. The reviewers evaluated all papers and sent the authors the comments on their work.The invited talks featured presentations of different European research projects: ELVIRE presented by Marc Brogle, EU-Mesh presented by Vasilios Siris, Frederica presented by Kurt Baumann, GINSENG presented by Marilia Curado, Socrates presented by Hans van den Berg, Winemo presented by Yevgeni Koucheryavy, and Wisebed presented by Torsten Braun.Luleå University of Technology is the northernmost university of technology in Scandinavia and with world-class research and education. Its strength lies in its cooperation with companies and with the rest of the world around it. ...